Digital Transformation of Higher Education in Sub-Saharan Africa: Challenges and Opportunities in Advanced Digital Skills - Saeid, Elsadig (Journal of Social Transformation and Regional Development, 2025)
The ongoing era of digital transformation has significantly altered the societal and economic landscape, profoundly impacting every aspect of daily life. This transformation has also highlighted the urgent need for both specialized digital skills and advanced digital skills. This paper addresses the gap in specific domain digital skills, advanced digital skills and the capacity for digital skills development within higher education institutions in sub-Saharan Africa. To this end, the average percentage of access to and attainment of tertiary education in sub-Saharan Africa is compared with that of the European Union. Furthermore, the capability for advanced skills development is assessed by comparing universities in sub-Saharan Africa with those in the European Union. The results indicate a significant gap in advanced digital skills between sub-Saharan Africa and the European Union. Additionally, higher education institutions in the European Union are more proficient in teaching, research, and industrial engagement than those in sub-Saharan Africa. Finally, a framework that emphasizes the use of technology, economics of sharing, and collaboration has been proposed to bridge this gap.